Construction and Demolition Waste Management (Tehran Case Study) - Rouhi Broujeni, B.; Omrani, G. A.; Naghavi, R.; Afraseyabi, S. S. (Engineering, Technology & Applied Science Research, 2016)
Increasing building construction raises concerns about construction and demolition (C&D) waste management. To assess this issue the building components, the collection schemes, their recycling and disposal should be investigated. In order to manage C&D wastes, paying attention to how this kind of wastes is disposed is imperative for their correct identification. Inattention, lack of organization and proper transport and sanitary disposal of construction and demolition waste lead to problems such as accumulation of construction waste in the streets. However, more than 90 percent of the potential for recycling and re-using as raw materials is provided. Environmental Protection Agency (EPA) has classified C&D wastes into three categories: non-dangerous waste, hazardous wastes and semi-hazardous wastes. Currently in Tehran, an average of about 50,000 tons per day of construction and demolition wastes are produced from which over 30,000 tons per day are dumped in landfills. According to this research more than 57% of these wastes are placed in the first category (non-dangerous waste) and have the potential for being recycled and reused. On the other hand, items that are placed in the second category shall be managed based on the existing laws. This article provides some management solutions including proposing methods for collecting and reusing construction waste in accordance with current market needs in Iran.